Neonatal Septicemia in Nepal: Early-Onset versus Late-Onset. (16th November 2015) - Ansari, Shamshul; Nepal, Hari Prasad; Gautam, Rajendra; Shrestha, Sony; Neopane, Puja; Chapagain, Moti Lal
Abstract : Introduction. Neonatal septicemia is defined as infection in the first 28 days of life. Early-onset neonatal septicemia and late-onset neonatal septicemia are defined as illnesses appearing from birth to three days and from four to twenty-eight days postnatally, respectively. Methods. In this cross-sectional study, blood samples from the suspected infants were collected and processed in the bacteriology laboratory. The growth was identified by standard microbiological protocol and the antibiotic sensitivity testing was carried out by modified Kirby-Bauer disk diffusion method. Results. Among total suspected cases, the septicemia was confirmed in 116 (12.6%) neonates. Early-onset septicemia (EOS) was observed in 82 infants and late-onset septicemia (LOS) in 34 infants. Coagulase-negative staphylococcus (CoNS) (46.6%) was the predominant Gram-positive organism isolated from EOS as well as from LOS cases followed by Staphylococcus aureus (14.6%). Acinetobacter species (9.5%) was the predominant Gram-negative organism followed by Klebsiella pneumoniae (7.7%). Conclusions. The result of our study reveals that the CoNS, Staphylococcus aureus, Acinetobacter spp., and Klebsiella pneumoniae are the most common etiological agents of neonatal septicemia. In particular, since rate of CoNS causing sepsis is alarming, prompting concern to curb the excess burden of CoNS infection is necessary.